If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -2) + 34x + -7 = 24x + -8 Reorder the terms: 5(-2 + 3x) + 34x + -7 = 24x + -8 (-2 * 5 + 3x * 5) + 34x + -7 = 24x + -8 (-10 + 15x) + 34x + -7 = 24x + -8 Reorder the terms: -10 + -7 + 15x + 34x = 24x + -8 Combine like terms: -10 + -7 = -17 -17 + 15x + 34x = 24x + -8 Combine like terms: 15x + 34x = 49x -17 + 49x = 24x + -8 Reorder the terms: -17 + 49x = -8 + 24x Solving -17 + 49x = -8 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. -17 + 49x + -24x = -8 + 24x + -24x Combine like terms: 49x + -24x = 25x -17 + 25x = -8 + 24x + -24x Combine like terms: 24x + -24x = 0 -17 + 25x = -8 + 0 -17 + 25x = -8 Add '17' to each side of the equation. -17 + 17 + 25x = -8 + 17 Combine like terms: -17 + 17 = 0 0 + 25x = -8 + 17 25x = -8 + 17 Combine like terms: -8 + 17 = 9 25x = 9 Divide each side by '25'. x = 0.36 Simplifying x = 0.36
| -7(7-3x)=-4(10-6x) | | 7a^2=19-8a | | x^2+.7x+.1=0 | | 8s(s+4)=s-21 | | 4(7-2b)+2(5b+2)= | | -0.2x-0.3y=0.2 | | -x+5-3x=-55 | | 5x-35=x-13 | | 10x=15x-15 | | 8x-6=5x-12 | | 2(23-x-2y)+2(23-x-7)=20 | | 4(x+3)=3x+3 | | 2(x+2)=3x-4 | | 2v+4=-2(2v+4) | | -6-7(5k-7)=3k-11(1+4k) | | 0=2x^3+8x+1 | | y=392-47.5x | | (-2*-2*-2*-2)-3(6+7)= | | 10=2x+8x | | 2+5r=26 | | 3n+24= | | x+y+2z=23 | | -1+x=x+11 | | x+6=1+2x+8 | | 0.16(y-8)+0.10y=0.18y-0.09(10) | | 11(-7n+4)=-23-11n | | 1.5k+3.5=-4 | | -3x-24=-6x+33 | | 10(1-p)=10(p+9) | | 12u+17y=891 | | 36b-9=18b+3 | | 27-2x=x |